Analysis of composites recycling and thermal oxidative treatments on carbon fibre - Heil, Joseph Paul (2016)
The process of carbon fibre composite recycling has been analysed and broken down into the thermal-kinetic behaviours of the constituent components of the composite and the reduction in mechanical properties of the recycled carbon fibres. Carbon fibre recycling has been a commercial operation since 2009 and the subject of extensive research for the last 10-15 years, with many years before that looking at glass fibre composites. However, very little work has been published regarding the optimization of the recycling process or a scientific explanation as to how the mechanical properties of the fibres are affected by the recycling. This research hypothesises that the tensile strength and elastic modulus are intimately linked to the microstructural changes that happen to the fibre as a result of its exposure to the hot oxidising environment used for carbon fibre recycling. To investigate this hypothesis a lab-scale carbon fibre recycling operation was built using a tube furnace and gas flow controllers. Carbon fibre-epoxy composites were recycled between 550oC and 650oC in varying oxygen concentrations between 0% and 21% for up to forty minutes to find recycling results representative of what is used commercially. Once this time, temperature, oxygen concentration parameter space was established, sized virgin fibres were recycled under these same conditions. Raman, XRD, XPS and single filament tensile testing were used to characterise the fibres before and after recycling. High strength and intermediate modulus fibres from both Hexcel and Toray were studied. Fibre type, fibre manufacturer, time, temperature, and oxygen concentration were used as factors in a design of experiments. Microstructural parameters, tensile strength, and elastic modulus were measured as responses. The microstructure of the recycled fibres was found to change in unpredictable ways. Temperature and the interaction of temperature with oxygen concentration were the most significant terms in the design of experiments. Time was not a significant factor on its own. AS4 and IM7 fibres from Hexcel were discovered to have an acute sensitivity to high temperatures and oxygen concentrations compared to T700 and T800S fibres from Toray. To better understand the recycling process itself a thermal-kinetic model is utilized to describe the oxidative decomposition of the composite. The recycling process is broken down into three reactions: pyrolysis, char oxidation, and fibre oxidation. TGA and DSC were used to characterise each of these reactions. The model uses a 1D finite difference method to predict the heat and mass flow through the composite over time. Temperature, composition of the composite, and mass flux are calculated for and between each of the model’s discrete layers. Any intermediate result may be printed to a text file for viewing or supplementary analysis. Most of the model parameters are based on user input, which makes the model a flexible and powerful tool for investigating carbon fibre composite recycling. The user defines the thickness and composition of the composite system of interest as well as the recycling time and operating temperature. Different resin systems can be studied as well as different thermal recycling methods by changing parameters in the model such as the heat transfer coefficient and defining what happens to the fibre once all the resin has been removed from it. For example, in the fluidised bed process the fibre leaves the recycling atmosphere, but for a belt furnace, fibre stays in the furnace for the entire duration of the process. The model is used to determine how long it takes for the pyrolysis and char oxidation reactions to occur which then tells how long a fibre is exposed to the recycling atmosphere for a process of a fixed duration.